Major Complications after Male Anti-Incontinence Procedures: Predisposing Factors, Management and Prevention - Romics, Miklos; Bánfi, Gergely; Keszthelyi, Attila; Klingler, Hans Christoph; Szarvas, Tibor; Szász, Marcell; Nyirády, Péter; Majoros, Attila (Urology Journal, 2020)
Purpose: Significant post-prostatectomy incontinence (PPI) is a crippling condition and managed best through sling or artificial urinary sphincter (AUS) implantation. These procedures are often associated with complications requiring surgical intervention. The aim of our retrospective study was to evaluate the occurrence of major complications and identify risk factors. Materials and Methods: Between 2010 and 2018 ninety-one patients have been implanted with sling (22; 24.2%) or AUS (69; 75.8%) in our department. The cases where surgical revision was needed were examined regarding the etiology (mechanical failure (MF), urethral erosion (UE), urethral atrophy (UA), surgical site infection (SSI), combined reasons (COMB) and analyzed, using 16 possible perioperative risk factors. Results: Surgical intervention was carried out by 19 / 91 (20.9%) patients. (In 16 / 69 cases after AUS (23.1%), 3 / 13 after slings (23%)). The indication was in 6 (31.6%) cases MF, in 3 (15.8 %) COMB, in 4 (21.1%) UE, in 5 (26.3 %) SSI, in 1 (5.2%) UA. The type of reoperation was either explantation (12 / 19), system replacement (6 / 19), or cuff replacement (1 /19). Regarding the surgical intervention requiring complications only preoperative bacteriuria (P = .006) and postoperative surgical site oedema (P = .002) proved to be independent predictive factors. Conclusion: Preoperative bacteriuria and surgical site oedema seemed to be good predictors for obligate surgical revision. Patients with AUS were more prone to have major complications. In most cases it was mechanical failure, infection or erosion. By reducing the frequency of these risk factors we might be able to decrease the amount of complications.